Obesity and diet independently affect maternal immunity, maternal gut microbiota and pregnancy outcome in mice - Wekema, Lieske; Schoenmakers, Sam; Schenkelaars, Nicole; Laskewitz, Anne; Liu, Lei; Walters, Lisa; Harmsen, Hermie J. M.; Steegers-Theunissen, Régine P. M.; Faas, Marijke M. (Frontiers in Immunology, 2024)
Introduction Maternal obesity poses risks for both mother and offspring during pregnancy, with underlying mechanisms remaining largely unexplored. Obesity is associated with microbial gut dysbiosis and low-grade inflammation, and also the diet has a major impact on these parameters. This study aimed to investigate how maternal obesity and diet contribute to changes in immune responses, exploring potential associations with gut microbiota dysbiosis and adverse pregnancy outcomes in mice. Methods Before mating, C57BL/6 mice were assigned to either a high-fat-diet (HFD) or low-fat-diet (LFD) to obtain obese (n=17) and lean (n=10) mice. To distinguish between the effects of obesity and diet, 7 obese mice were switched from the HFD to the LFD from day 7 until day 18 of pregnancy (“switch group”), which was the endpoint of the study. T helper (Th) cell subsets were studied in the spleen, mesenteric lymph nodes (MLN) and Peyer’s patches (PP), while monocyte subsets and activation status were determined in maternal blood (flow cytometry). Feces were collected before and during pregnancy (day 7,14,18) for microbiota analysis (16S rRNA sequencing). Pregnancy outcome included determination of fetal and placental weight. Results Obesity increased splenic Th1 and regulatory T cells, MLN Th1 and PP Th17 cells and enhanced IFN-γ and IL-17A production by splenic Th cells upon ex vivo stimulation. Switching diet decreased splenic and PP Th2 cells and classical monocytes, increased intermediate monocytes and activation of intermediate/nonclassical monocytes. Obesity and diet independently induced changes in the gut microbiota. Various bacterial genera were increased or decreased by obesity or the diet switch. These changes correlated with the immunological changes. Fetal weight was lower in the obese than the lean group, while placental weight was lower in the switch than the obese group. Discussion This study demonstrates that obesity and diet independently impact peripheral and intestinal immune responses at the end of pregnancy. Simultaneously, both factors affect specific bacterial gut genera and lead to reduced fetal or placental weight. Our data suggest that switching diet during pregnancy to improve maternal health is not advisable and it supports pre/probiotic treatment of maternal obesity-induced gut dysbiosis to improve maternal immune responses and pregnancy outcome.